Penerapan Metode Simulasi Melalui Sidang Parlemen dalam Meningkatkan Kemampuan Kognitif (Berpikir Kritis dan Logis) pada Peserta Didik Kelas XI MIPA 1 MAN Insan Cendekia Pasuruan - Nafisah, Hurrotun; Fatmawati, Lailil (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to improve students' cognitive abilities through the implementation of the parliamentary session simulation method in Class XI MIPA 1 at MAN Insan Cendekia Pasuruan. The cognitive abilities in focus include critical and logical thinking skills. The study employs Classroom Action Research (CAR), conducted in two cycles, each comprising planning, implementation, observation, and reflection stages. The data source consists of students from Class XI MIPA 1 at MAN Insan Cendekia Pasuruan. The learning process was enhanced through engaging activities using parliamentary session simulation media tailored to the learning theme. The findings indicate that this method effectively improves students' critical and logical thinking skills, as evidenced by observational data collected during learning activities. In the first cycle, the learning improvement rate reached 50%, while in the second cycle, it increased to 82.05%, surpassing the research success indicator of 80%. These results suggest that the parliamentary session simulation method can serve as an alternative instructional approach to enhance students' cognitive abilities in critical and logical thinking.